Unveiling the hidden link between oral flora and colorectal cancer: a bidirectional Mendelian randomization analysis and meta-analysis - Zhang, Zexin; Wu, Wenfeng; Xiahou, Zhikai; Song, Yafeng (Frontiers in Microbiology, 2024)
The impact of oral flora on intestinal micro-environment and related diseases has been widely reported, but its role in colorectal cancer (CRC) remains elusive.Methods: A Two-sample Mendelian Randomization (TSMR) analysis was conducted to explore the causal relationship between oral flora and CRC, with the Inverse-Variance Weighted (IVW) serving as the primary method for evaluating this causal relationship. Data on the oral flora were derived from human samples from the tongue and saliva, with all cohort populations originating from Asia. In addition, 2 independent external cohorts were used to validate the positive results and perform a meta-analysis of the final results. Lastly, to balance the effect of positive oral flora on CRC, a Multivariate Mendelian Randomization (MVMR) analysis was also performed.The TSMR analysis revealed that 17 oral flora may have a causal relationship with CRC in the training cohort. Among them, s Haemophilus, g Fusobacterium, s Metamycoplasma salivarium, and s Mogibacterium pumilum were validated in two testing cohorts. Intriguingly, after integrating the results of the 3 cohorts for meta-analysis, 16 associations remained significant. In the training cohort, MVMR analysis demonstrated that s Capnocytophaga ochracea and s Metamycoplasma salivarium retained statistical significance. In one of the testing cohorts, s Metamycoplasma salivarium, s Streptococcus anginosus, and s Streptococcus sanguinis retained statistical significance. In the other testing cohort, s Metamycoplasma salivarium, s Haemophilus, and g Fusobacterium remained significant. Conclusions: s Haemophilus, g Fusobacterium, s Metamycoplasma salivarium, and s Mogibacterium pumilum have a solid causal relationship with the occurrence and development of CRC.